2022
DOI: 10.4018/ijgbl.2020040102
|View full text |Cite
|
Sign up to set email alerts
|

Can Video Gameplay Improve Undergraduates' Problem-Solving Skills?

Abstract: In this study, the authors investigated if two distinct types of video gameplay improved undergraduates' problem-solving skills. Two groups of student participants were recruited to play either a roleplaying video game (World of Warcraft; experimental group) or a brain-training video game (CogniFit; control group). Participants were measured on their problem-solving skills before and after 20 hours of video gameplay. Two measures were used to assess problem-solving skills for this study, the Tower of Hanoi and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In experimental studies, eight out of 19 studies found that a video game intervention led to more improvements on at least one problem solving task compared to active or passive control groups (Adams et al, 2016;Baniqued et al, 2014;Basak et al, 2008;Bejjanki et al, 2014;Boot et al, 2008;Buelow et al, 2015;Colom et al, 2012;Emihovich et al, 2020;Libertus et al, 2017;Maillot et al, 2012;Marra, 2016;Masson et al, 2011;Minear et al, 2016;Nouchi et al, 2013;Novak & Tassell, 2015;Pilegard & Mayer, 2018;Shute et al, 2015;Valadez & Ferguson, 2012;Whitlock et al, 2012). However, out of 60 comparisons across these studies, 44 resulted in no differences between experimental and control groups across all problem solving tasks.…”
Section: Entertainment Video Games and Problem Solvingmentioning
confidence: 99%
“…In experimental studies, eight out of 19 studies found that a video game intervention led to more improvements on at least one problem solving task compared to active or passive control groups (Adams et al, 2016;Baniqued et al, 2014;Basak et al, 2008;Bejjanki et al, 2014;Boot et al, 2008;Buelow et al, 2015;Colom et al, 2012;Emihovich et al, 2020;Libertus et al, 2017;Maillot et al, 2012;Marra, 2016;Masson et al, 2011;Minear et al, 2016;Nouchi et al, 2013;Novak & Tassell, 2015;Pilegard & Mayer, 2018;Shute et al, 2015;Valadez & Ferguson, 2012;Whitlock et al, 2012). However, out of 60 comparisons across these studies, 44 resulted in no differences between experimental and control groups across all problem solving tasks.…”
Section: Entertainment Video Games and Problem Solvingmentioning
confidence: 99%
“…Conversely, certain studies indicate that engaging in video game play may potentially yield beneficial effects on one's attention span. Specific categories of video games, including strategy and puzzle games, necessitate players to partake in critical thinking and problem-solving exercises, which have the potential to enhance cognitive capacities associated with concentration and attention (8,9). By requiring players to engage in strategic thinking and premeditation, these games have the potential to improve attention abilities in a manner that is applicable to practical endeavors that demand constant focus.…”
Section: Effects Of Video Games On Attention Spanmentioning
confidence: 99%
“…The results show that LSTM-based model outperformed the previous state-of-the-art approach in providing more accurate predictions of students' post-competencies. The authors in Emihovich et al (2020) attempted to find the impacts of video gameplay on students' problem-solving skills. Undergraduate students were required to play either a roleplaying game or a brain-training game.…”
Section: Related Workmentioning
confidence: 99%